Time-resolving small angle X-Ray scattering analysis of melt crystallization of mixtures of regular and irregular isotactic polypropylene samples. (12th February 2021) - Auriemma, Finizia; Ruiz de Ballesteros, Odda; Giusto, Giovangiuseppe; Di Girolamo, Rocco; Malafronte, Anna; Scoti, Miriam; De Rosa, Claudio; Mitchell, Geoffrey R.
Abstract : The melting/crystallization properties of blends obtained by mixing two isotactic polypropylene (iPP) samples synthesized using single-site metallocene catalyst systems and containing a high and low concentration of rr triads as stereo-defects, are studied. The changes occurring at lamellar length scale during a heating/cooling cycle at constant scanning rate are followed in situ by performing time-resolved small angle X-ray scattering (SAXS) measurements. Data analysis demonstrates that the evolution of the SAXS intensity with increase/decrease of the temperature is controlled by the separate melting/crystallization of the two components, the differences in the thermal expansion (contraction) coefficient of the amorphous and crystalline phases and the role of thermal fluctuations in electron density. The two components give rise to different populations of intermixed lamellar stacks in the blends which originate from the good miscibility of the low and high stereoregular samples in the melt. Highlights: Blends of a high and a low stereoregular isotactic polypropylene are analyzed. SAXS probes the separate melting/crystallization of the components. The good miscibility in the melt induce formation of intermixed lamellar stacks. SAXS also probes thermal fluctuations in electron density. The high temperature SAXS analysis provides information about the melt strength.